Construct Validity and Reliability of a Researcher-Made Muscular–Motor Readiness Assessment Tool for Children Aged 3–7 for Specialized Instrument Training - Peyvandzadeh, Younes (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The study aimed to examine the construct validity and reliability of a researcher-made muscular–motor readiness assessment tool designed to evaluate the preparedness of children aged 3–7 years for specialized musical instrument training.Methods and Materials: This methodological study was conducted in 2025 in Mashhad using a multi-stage cluster sampling procedure. A total of 251 children aged 3–7 years who were enrolled in music-education programs participated in the study. The researcher-developed assessment tool was designed based on an integrated framework derived from the Denver II, the Movement Assessment Battery for Children-2 (MABC-2), and the Bruininks–Oseretsky Test of Motor Proficiency-2 (BOT-2). The instrument evaluated fine and gross motor coordination, postural stability, visual–motor integration, muscle tone, and motor sequencing abilities relevant to early instrumental performance. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed to evaluate construct validity. Reliability and convergent validity were assessed using Cronbach’s alpha, composite reliability (CR), and average variance extracted (AVE). Data analyses were conducted using SPSS and SmartPLS version 4.Findings: Exploratory factor analysis identified four underlying factors that collectively explained 79.7% of the total variance. Confirmatory factor analysis supported the four-factor structure, with all factor loadings statistically significant (p < .001). Reliability analysis demonstrated strong internal consistency, with Cronbach’s alpha coefficients ranging from 0.805 to 0.971 and composite reliability values ranging from 0.909 to 0.984. Convergent validity was confirmed through AVE values between 0.759 and 0.926. Furthermore, discriminant validity was supported by both the Fornell–Larcker criterion and HTMT ratios below the recommended threshold.Conclusion: The findings indicate that the researcher-made muscular–motor readiness assessment tool possesses satisfactory construct validity, reliability, convergent validity, and discriminant validity for evaluating children’s readiness for specialized musical instrument training.